Pendampingan Masyarakat Desa Sungai Rengas Sebagai Upaya Peningkatan Kesadaran Akan Pentingnya Kesehatan Mental - Pratiwi - Apridamayanti; Sabina - Heryani; Murniati - Murniati; Sisilia - Grasella; Desta Arilia Syafitri (Universitas Tanjungpura, 2023)
Mental health is a form of balance between mental functions and the creation of adjustments between humans and themselves and their surroundings. Awareness of the importance of mental health, especially in Indonesia, is still very low, people should educate each other to increase understanding and knowledge and awareness of mental health. So that real work lecture activities are carried out which are community service activities in certain areas with the aim of helping the community in increasing the level of knowledge and skills with the hope of increasing people's welfare. The implementation of this service is in Sungai Rengas Village, Sungai Kakap District, Kubu Raya Regency, West Kalimantan Province with a program that places more emphasis on the theme of mental health. The programs carried out include providing education to the children of Rengas Hamlet, assisting in the implementation of Posyandu, planting family medicinal plants (TOGA), exercising & playing with children, and making aromatherapy candle products from used cooking oil. In general, community service activities in Sungai Rengas Village went very well and smoothly. This is because the enthusiasm of the community is very good, so that the implementation runs smoothly and what we hope is that these programs can be of benefit to the local community.